Information Fusion-Based Optimal Attitude Control for an Alterable Thrust Direction Unmanned Aerial Vehicle. (16th January 2013) - Zhen, Ziyang; Jiang, Ju; Wang, Xinhua; Wang, Daobo
Attitude control is the inner-loop and the most important part of the automatic flight control system of an unmanned aerial vehicle (UAV). The information fusion-based optimal control method is applied in a UAV flight control system in this work. Firstly, a nonlinear model of alterable thrust direction UAV (ATD-UAV) is established and linearized for controller design. The longitudinal controller and lateral controller are respectively designed based on information fusion-based optimal control, and then the information fusion flight control system is built up. Finally, the simulation of a nonlinear model described as ATD-UAV is carried out, the results of which show the superiority of the information fusion-based control strategy when compared to the single-loop design method. We also show that the ATD technique improves the anti-disturbance capacity of the UAV.